A INCIDENCE, PREVALENCE, AND CLINICAL MANAGEMENT OF POISONING CASES IN TELANGANA STATE REGION – A PROSPECTIVE STUDY - HARISHWARREDDY, POTHULA; D, NAGALATHA; G, VEENA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: This study aimed to find the incidence, prevalence, and clinical management of poisoning cases in Telangana state region. Methods: It was a prospective and observational study done for 9 months and the data were obtained from the case sheets of 600 patients admitted in tertiary care hospital with poisoning. Data were analyzed according to age, gender, type and route of poisoning, treatment of poisoning, and mortality and morbidity rate. Results: Out of 600 cases admitted, female patients were 312 (52%) and males were 288 (48%) and the age group ranged from 6 months to 70 years of age. The most common route of exposure was ingestion (oral) (91.5%) followed by topical (dermal) (8%), and the agents which were used included organophosphate (33%) in most of the cases followed by chemical poisoning (24%). The average duration of therapy till the discharge of the patients was 1–5 day. About 80% of the cases were from the low socioeconomic background. More or less, the treatment is restricted to symptomatic and supportive care if the poisonous agent is unknown. A specific antidote is given, where there is enough information regarding the poison. Conclusion: The present study revealed increasing incidence of poisoning cases from rural areas and below the poverty line due to lack of knowledge, easy availability, stress, depression, and familial disharmony. By providing educational, awareness programs, and establishing a poison information center, there is a possibility for a decline in the incidence of poisoning.